El Impacto de la Gestión de Riesgos en las Organizaciones: Una revisión de la literatura - Collins Estrada, Renzo Martin (2023)
Events in the early years of the 21st century, such as the Enron and WorldCom scandals and the financial crises, revealed significant deficiencies in existing control processes and the difficulties companies had in structuring robust risk management models. With the advent of COSO ERM, ISO 31000 and the Sarbanes Oxley Act –as the main frameworks for holistic risk management models– the aim was for organizations to improve their ability to achieve their strategic objectives through activities that manage uncertainty and, above all, create and sustain organizational value. The purpose of this paper is to review the research on the effectiveness of risk management in organizations by reviewing the literature in Scopus and Web of Science. This review shows that the research is not conclusive regarding the real impact generated by risk management systems and their contribution to value creation and increase in financial profitability. It also shows that there is an interesting gap for future research, considering that many of the studies that have been carried out have a special emphasis on the financial sector, neglecting other equally important economic sectors.